Filibusters and expansionists : Jeffersonian manifest destiny, 1800-1821 - Owsley, Frank Lawrence, Jr., 1928-2013 (University of Alabama Press, 1997)
The first two decades of the 19th century found many Americans eager to move away from the crowded eastern seaboard and into new areas where their goals of landownership might be realized. Such movement was encouraged by Presidents Jefferson, Madison, and Monroe - collectively known as the Jeffersonians - who believed that the country's destiny was to have total control over the entire North American continent. The Jeffersonian presidents would have used any means, short of all-out war, to expand the boundaries of the United States. Filibusters and Expansionists explores the motives of those presidents in office during that time and also the successful and unsuccessful intrigues and episodes of the movement.